Correlations between immunogenicity, drug levels, and disease activity in an Italian cohort of rheumatoid arthritis patients treated with tocilizumab - Benucci M (Dove Medical Press, 2016)
Maurizio Benucci,1 Francesca Meacci,2 Valentina Grossi,2 Maria Infantino,2 Mariangela Manfredi,2 Emanuele Bellio,2 Valerio Bellio,2 Francesca Li Gobbi,1 Laura Bazzichi,3 Paolo Moscato,4 Dario Caputo,4 Gianantonio Saviola,5 Rossella Talotta,6 Piercarlo Sarzi-Puttini,6 Fabiola Atzeni71Rheumatology Unit, Ospedale San Giovanni di Dio, Florence, Italy; 2Allergology and Immunology Laboratory, Ospedale San Giovanni di Dio, Florence, Italy; 3Rheumatology Unit, University of Pisa, Pisa, Italy; 4Internal Medicine and Rheumatology Unit, University of Salerno, Salerno, Italy; 5Rheumatology Unit, Salvatore Maugeri Foundation, Mantua, Italy; 6Rheumatology Unit, Ospedale Luigi Sacco, Milan, Italy; 7IRCCS Galeazzi Orthopedic Institute, Milan, ItalyAbstract: The aim of this study was to evaluate the real-life immunogenicity of anti-drug antibodies, drug levels, and disease activity in an Italian cohort of rheumatoid arthritis patients treated with tocilizumab (TCZ). We evaluated 126 TCZ-treated patients with rheumatoid arthritis (16 males and 110 females; mean age 59±12 years, range 26–83; mean disease duration 11±5 years) with inadequate 12-week response to any synthetic and biological disease-modifying anti-rheumatic drugs, in a retrospective analysis. One-hundred and seven patients were treated with methotrexate mean dose 12.6±1.3 mg/week in combination with TCZ, 13 received TCZ monotherapy, and six received leflunomide 20 mg/day plus TCZ; all patients were treated with prednisone mean dose 6.4±1.2 mg/day. They had a 28-joint Disease Activity Score (DAS28) of >3.2, an erythrocyte sedimentation rate (ESR) of >30 mm/hour, and CRP levels of >1.0 mg/dL. We evaluated at baseline and after 6 months of treatment: DAS28; rheumatoid factor (RF) IgM, IgA, and IgG; anti-citrullinated peptide antibody; ESR; CRP; TNF-α; and IL-6. TCZ and anti-TCZ antibodies were detected using LISA-TRACKER Duo TCZ. TCZ levels of <10 µg/mL were considered low and >10 µg/mL high. After 6 months of treatment only one patient was positive for anti-TCZ antibodies. There were correlations between DAS28, ESR, and CRP and IL-6 levels in all patients. Comparison of the 84 patients with TCZ levels of <10 µg/mL and the 42 with TCZ levels of >10 µg/mL showed the following differences: DAS28: 3.09±1.32 vs 2.78±1.32, P=0.0005; ESR: 27±14.8 vs 14±12 mm/hour, P=0.0001; CRP: 1.47±1.05 vs 0.65±0.80 mg/dL, P=0.0086; TNF-α: 10.2±1.2 vs 9.9±1.1 pg/mL, P=0.999; IL-6: 3.65±4.75 vs 3.62±4.41 pg/mL, P=0.97; anti-citrullinated peptide antibody: 85.2±93.7 vs 86.7±90.3 IU/mL, P=0.94; RF IgM: 72.4±62.7 vs 68.3±61.6 IU/mL, P=0.754; RF IgA: 41.7±36.4 vs 47.8±42.1 U/mL, P=0.449; and RF IgG: 46.4±46.1 vs 59.3±58.2 U/mL, P=0.212. These findings show that the occurrence of anti-drug antibodies against TCZ is very rare and that there are statistically significant correlations between TCZ levels of >10 µg/mL and ESR, CRP levels, and DAS28.Keywords: tocilizumab, TCZ drug level, antibodies anti-TCZ